Ambiguitas Norma Pendidikan Antikorupsi di Perguruan Tinggi, Antara Kewajiban dan Kebutuhan - Muammar; Taufik, Iqbal (Pustaka Peradaban, 2023)
This paper aims to describe and analyze the ambiguity of norms in Anti-Corruption Education in tertiary institutions. The study uses a conceptual approach (conceptual approach) and an analytical approach (analytical approach). This paper finds that normatively there is ambiguity in Anti-Corruption Education norms in the legal basis for implementing anti-corruption education in tertiary institutions. The ambiguity in question is that there is a contradiction of norms as stipulated in Article 2 paragraph 1 which obligatively on the one hand requires tertiary institutions to provide anti-corruption education through courses, either independently or by insertion. However, on the other hand, in Article 3, paragraph 1, the phrase used in the article weakens the article. Another ambiguity is that anti-corruption education norms seem